Preservation of socioemotional wealth and professionalization in family businesses - Ames, Alice Carolina (2020)
Family businesses dominate business in most of the world's economies, influencing the social-economic environment. This study aims to investigate how socioemotional wealth impacts the professionalization process in a family business. The research is characterized as exploratory, a qualitative case study carried out in a company located in Santa Catarina with 50 years of history, being a large-scale, privately-held company. The interviews were analyzed using the discourse analysis approach. The results of the research suggest that socioemotional wealth influenced professionalization to preserve family values, given that professionalization occurred to maintain and survive the business. Also, the hiring of non-family professionals allowed different perceptions for decision making, adding value to decision making. The theoretical contribution of the study consists of the discussion of socioemotional wealth and professionalization, about the involvement of the family in the organization, and the participation of non-family professionals in the management of the business, taking into account that the socioemotional wealth reinforces the professionalization of the family business. This study broadens the debate about professionalization in family businesses, suggesting that this process does not compete with the maintenance of socioemotional wealth.